Theoretical and experimental study of solar cells based on nanostructured films of TiO2 sensitized with natural dyes extracted from Zea mays and Bixa orellana - Huamán Aguirre, Arnold Anthony (2021)
The authors gratefully acknowledge support from the PhD program in Physics of the National University of Engineering financed by CONCYTEC through Resolution No. 197-2015.